Domestic Violence Against Women: Policy, Practice and Solutions in the Australian Context - Chung, Donna; Wendt, S. (Federation Press, 2015)
The chapter provides an overview of domestic violence in Australia including an examination of the definition, prevalence, the impacts on women and children and key policy and practice responses to end such violence.